(untitled) (Rudarsko-geološko-naftni zbornik, 2018)
Geophysical subsurface investigations use the principles of physics to unravel intrinsic Earth’s subsurface features and nature of the underlying geology. Over the past two decades, the use of Seismic Refraction Tomography (SRT) and Elec- trical Resistivity Tomography (ERT) for subsurface investigations has greatly improved the quality of acquired data for two- and three-dimensional (2D and 3D) surveys. SRT employs more shotpoints and receivers than the conventional seismic refraction for its imaging technique. ERT uses automated multi-electrode array systems to improve the confi- dence of large and dense data collection. SRT and ERT techniques use powerful inversion algorithms to achieve high resolution subsurface inversion models for resolving subsurface characteristics and geological conditions over a complex and larger area that may be difficult with the use of their conventional methods. The 2D and 3D inversion models (tomo- grams) generated from the field data sets of these techniques efficiently ameliorate inaccurate subsurface boundaries and structural delineation with higher depth resolution, especially the 3D inversion models for areas of complex geology. These state-of-the-art techniques have extensively been used for groundwater, environmental, engineering and mining investigations among others. This study provides insight from theories to data inversion techniques for the known to- mography techniques (SRT and ERT) in use for subsurface investigations.